Pengaruh gerakan sujud dalam sholat untuk meningkatkan sirkulasi darah pada otak - Pratiwi, Nanda Novitasari Indah (Maliki Interdisciplinary Journal, 2025)
Prayer is a mandatory worship that must be carried out by every Muslim, this practice will be the first to be performed when in the hereafter. Prayer as a mandatory worship not only has spiritual value, but also provides benefits for the health of the human body. Prayer is a series of movements starting with a standing position, then bending until the hands reach the knees, and then continuing to stand up again. Movement in prayer has a positive influence on the health of the human body. One of them is the prostration movement which provides benefits for the health of the human body, namely increasing blood circulation in the brain. This journal discusses the effect of prostration movements in prayer to increase blood circulation in the brain. The method used in this study is a literature study by accumulating, studying, and analyzing information from written sources in the form of books and journals. Prayer is often only as fulfilling the obligations of the sharia without paying attention to perfection in the movement. The existence of an understanding of the benefits of prostration movements in prayer for the body to increase blood circulation is expected to motivate a person to carry out prayers properly and correctly.